2017
DOI: 10.1161/jaha.116.005179
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Carotid Plaque Score and Coronary Artery Calcium Score for Predicting Cardiovascular Disease Events: The Multi‐Ethnic Study of Atherosclerosis

Abstract: Background--Coronary artery calcium (CAC) predicts coronary heart disease (CHD) events better than carotid wall plaque presence; however, differences in the utility of CAC burden and carotid plaque burden across the spectrum of cardiovascular disease (CVD) events is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 30 publications
3
88
1
2
Order By: Relevance
“…3 CAC has already been shown to be a stronger predictor of CHD than stroke. 4,5 The fact that more patients have CT scans with thoracic ECC than CAC, make thoracic ECC scoring a valuable method to be studied and utilized for patient risk assessment. Although CAC=0 is deemed to predict lower CVD risk 26 , Wong et al showed that more than 55% of MESA participants had extra-coronary calcification that may put them at high risk for CVD events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 CAC has already been shown to be a stronger predictor of CHD than stroke. 4,5 The fact that more patients have CT scans with thoracic ECC than CAC, make thoracic ECC scoring a valuable method to be studied and utilized for patient risk assessment. Although CAC=0 is deemed to predict lower CVD risk 26 , Wong et al showed that more than 55% of MESA participants had extra-coronary calcification that may put them at high risk for CVD events.…”
Section: Discussionmentioning
confidence: 99%
“…2 The 2013 American College of Cardiology/American Heart Association (ACC/AHA) guidelines placed an emphasis on the prediction of both CHD and stroke events. 3 However, CAC is a stronger predictor of CHD 2 than stroke 4, 5 . Therefore, further risk information, in particular other imaging data, may be needed beyond CAC to enhance prediction of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Reread examination 1 IMT and plaque measurements were used in our analyses to ensure consistency with examination 5 measures; they also were more reproducible and plaque assessments were more concordant with clinical consensus recommendations than original measurements. Details of ultrasound IMT and plaque rereadings have been described previously . The small number of participants with ultrasound data at only examination 5 (N=5) were excluded from IMT and plaque analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Carotid plaque presence was defined as a discrete focal wall thickening ≥1.5 mm or focal wall thickening ≥50% of the surrounding IMT . A carotid plaque score was used in our main analyses and calculated as the total number of plaques in the internal, bifurcation, and common carotid artery segments (range, 0–12) . Carotid plaque scores were available for 4319 participants with apolipoprotein measurements at baseline and 2753 participants at examination 5.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Cao and colleagues showed that the presence of intermediate and high-risk carotid plaque on carotid ultrasound conferred approximately a 2-fold increased risk of CVD event after adjustment for traditional CVD risk factors in the Cardiovascular Health Study, a study of adults (≥ 65 years) without known CVD 10 . In the younger Multi-Ethnic Study of Atherosclerosis (MESA) cohort study, carotid plaque score was also a significant predictor of CVD events after adjustment for traditional risk factors (HR 1.27, 95% CI 1.16–1.40, p< 0.001) 11 . The observed link between asymptomatic carotid plaque and subsequent CVD events in a cohort of persons living with HIV supports the potential utility of carotid plaque measurements as a biomarker of CVD risk stratification and CVD risk reduction.…”
mentioning
confidence: 99%